Association between triglyceride-glucose index multiplied by waist circumference and H-type hypertension among Chinese adults - Yiwei Peng; Yiwei Peng; Yiwei Peng; Yiwei Peng; Ling Li; Ling Li; Ling Li; Minqi Li; Minqi Li; Minqi Li; Jie Wang; Jie Wang; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundsThe triglyceride-glucose index combined with waist circumference (TyG-WC) has good predictive performance for cardiovascular disease, but the relationship of TyG-WC with H-type hypertension (HTH) is still unclear.ObjectsTo explore the association between TyG-WC and HTH, and provide theoretical basis for the prevention and treatment of HTH in the community population.MethodsThe study used multi-stage cluster random sampling to collect representative samples from urban and rural populations in Hunan Province. HTH was defined as primary hypertension with homocysteine ≥15 μmol/L. Logistic regression and restricted cubic spline (RCS) models analyzed the TyG-WC index's association with HTH. Receiver operating characteristic (ROC) curve analysis compared TyG, WC, TyG-BMI, and TyG-WC in diagnosing HTH. An additive interaction analysis evaluated the synergistic effect of TyG and WC on HTH. Comparative analyses were conducted on the association between the TyG-WC index and both types of hypertension in the general population.Results4,012 subjects were included in this study, and the prevalence of HTH was 19.77%. After adjusting for multiple confounding factors, participants with the highest quartile of TyG-WC had a higher risk of developing HTH compared to those with the lowest quartile of TyG-WC, with OR values of 3.182 (95% CI: 2.370–4.272, P < 0.001). RCS analysis revealed a significant correlation between TyG-WC index and HTH (overall trend P < 0.001). The correlation between TyG-WC and HTH still existed in subgroup analysis. ROC curve analysis showed that TyG-WC has higher predictive value for HTH compared to other variables (AUC = 0.676, 95%CI: 0.655–0.696, P = 0.010). Interaction analysis showed an additive effect between TyG and WC, with individuals having both high TyG and high WC exhibiting a 1.66 times higher HTH risk than those with low TyG and low WC. TyG-WC demonstrated a stronger association with HTH than with general hypertension.ConclusionThe TyG-WC index has high predictive value in identifying HTH, being a promising biomarker for HTH. Our findings provide theoretical basis for the prevention and treatment of HTH in the community population by controlling blood lipid, blood glucose, and waist circumference levels.